Implementation of Management Functions in Educational Institutions at MISS Al – Khairiyah Sunggal - Tarigan, Audia Amanda Br; Kabry, Futhri Raudhatul; Kahairuman, M. Farhan; Aini, Nur; Lubis, Zulfikar; Siahaan, Amiruddin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
In the implementation of management in an education, it is needed to achieve the educational goals, this research uses a descriptive qualitative research method. Qualitative research, namely, research that does not use calculations, data collection techniques are carried out in a triangulation manner, the data obtained tends to be qualitative data, the results of qualitative research are to understand meaning, understand uniqueness, construct phenomena and find hypotheses. An educational institution, or educational institution, is an organization or a group of people that for one reason or another is responsible for the education of students in accordance with the mission of the institution. The management function in the educational institution at MIS Al-Khairiyah Sunggal has all been carried out well, including the planning function where a good plan greatly affects the success of the work.